Reconstruction of Large Skeletal Defects: Current Clinical Therapeutic Strategies and Future Directions Using 3D Printing - Vidal, Luciano; Kampleitner, Carina; Brennan, Meadhbh Á.; Hoornaert, Alain; Layrolle, Pierre (Frontiers in Bioengineering and Biotechnology, 2020)
The healing of bone fractures is a well-orchestrated physiological process involving multiple cell types and signaling molecules interacting at the fracture site to replace and repair bone tissue without scar formation. However, when the lesion is too large, normal healing is compromised. These so-called non-union bone fractures, mostly arising due to trauma, tumor resection or disease, represent a major therapeutic challenge for orthopedic and reconstructive surgeons. In this review, we firstly present the current commonly employed surgical strategies comprising auto-, allo- and xenograft transplantations, as well as synthetic biomaterials. Further to this, we discuss the multiple factors influencing the effectiveness of the reconstructive therapy. One essential parameter is adequate vascularization that ensures the vitality of the bone grafts and thereby supports the regeneration process, with deficient vascularization presenting as a serious problem frequently encountered in current management strategies. To address this challenge, vascularized bone grafts, including free or pedicled fibula flaps, or in situ approaches using the Masquelet induced membrane, or the patient`s body as a bioreactor, comprise feasible alternatives. Finally, we highlight future challenges and novel strategies such as 3D printing and bioprinting which could overcome some of the current challenges in the field of bone defect reconstruction, with the benefit of fabricating personalized and vascularized scaffolds